Upper Vipava Valley as a promising tourist destination: Opportunities and challenges in tourism and the impacts of climate change - Princes Ledinek, Tisa (Journal for Geography, 2026)
The Upper Vipava Valley holds exceptional potential to develop into an exclusive tourist destination, thanks to its natural assets, which are only now beginning to be fully recognised. Currently in the early stages of tourism development, the region is shifting towards more sustainable and eco-friendly practices, bringing both challenges and numerous opportunities. Over the past decade, the area has undergone noticeable changes, driven by increased tourism activity and the effects of climate change. The Upper Vipava Valley has evolved from a visually less attractive destination into a sophisticated and appealing nexus of viticulture, gastronomy and outdoor recreation. This initial phase of tourist development is critical: the Upper Vipava Valley can either advance to a high-end tourist centre or remain in the limited and unrealised stages of its tourism potential.